Dissecting insects as sustainable protein bioresource in fish feed for aquaculture sustainability - Nitesh Kumar Yadav; Mutum Deepti; Arun Bhai Patel; Parvind Kumar; Jaya Angom; Sourabh Debbarma; Soibam Khogen Singh; Suparna Deb; Jham Lal; Anand Vaishnav; Rupali Das; Shubham Kashyap; et al. (Discover Food, 2025)
Abstract Insect based feeds (entofeeds) are emerging as a promising alternative for aquaculture nutrition, offering numerous advantages over conventional feed sources. This review assesses the nutritional composition of entofeeds, highlighting their rich protein content, essential amino acid profiles, healthy lipid compositions, as well as micronutrients. Compared to traditional feeds like fish meal, entofeeds have a great potential in reducing reliance on marine resources while minimizing environmental impacts, including land, water, and energy use. Additionally, their ability to upcycle organic waste supports the concept of circular economy. The review also explores feeding trials in various aquaculture species, demonstrating positive outcomes in growth performance, feed conversion efficiency, and immune health. Despite these advantages, entofeeds face challenges related to regulatory approvals, cost-effectiveness, and consumer acceptance. This review identifies areas for future research, including optimizing entofeeds formulations, scaling production, and enhancing their integration into sustainable aquaculture practices. Ultimately, entofeeds hold significant potential to address current sustainability challenges in aquaculture while shaping the future of animal feed.